MENCIPTAKAN BUDAYA RELIGIUS DI LINGKUNGAN PENDIDIKAN MELALUI PEMBOBOTAN PERAN PENDIDIK SEBAGAI MAKELAR BUDAYA - Momy A. Hunowu (Irfani, 2018)
There are three educational environments namely family, school and community environment. They can create a good generation or a bad generation. It depends on the role of educators. They can create a religious or non-religious environment. The educators are parents, teachers and community leaders. They can act as cultural brokers to protect the generation from the impact of globalization by means of creating religious culture.